Religious Social Values in the Wiridan Tradition in the Village of Lubuk Bayas, North Sumatra - Alzamzami, Mutaqin; Ashani, Sholahuddin; Ade Syahputra, Rizki (KARSA Journal of Social and Islamic Culture, 2021)
This article describes the wiriddan tradition carried out by the community in Lubuk Bayas Village, North Sumatra. The focus of this study is on two wiriddan traditions, which take place twice a week, once especially for male congregations and another day specifically for female congregations. This research uses interview, observation, and descriptive analysis methods. In this tradition, the congregation usually reads surah yasin, al-ikhlash, al-falaq, al-nas and takhtim takhlil. Wiriddan activities take place at the house of a community by applying a rotating system. Through the interview method, the writer can classify several social values that are considered by the community to be very important and make it a motivation to continue to carry out the wiriddan tradition. The socio-religious values that are felt by the community, including the moment of gathering, the opportunity to give alms, mutual assistance, respect for teachers, a forum for dialogue between residents, and through this way, they can strengthen brotherhood, especially between neighbors.